Effect of Yield Power Law Fluid Rheological Properties on Cuttings Transport in Eccentric Horizontal Narrow Annulus. (3rd July 2016) - Ofei, Titus Ntow
Abstract : Narrow annular drilling such as casing-while-drilling technique is gaining popularity due to its ability to mitigate nonproductive time during oil and gas drilling operations. However, very little is known about the flow dynamics in narrow annular drilling. In this study, the Eulerian-Eulerian two-fluid model was used to examine the influence of Yield Power Law fluid rheological properties on cuttings transport in eccentric horizontal narrow annulus. The flow was assumed as fully developed, laminar, and transient state. The present simulation model was validated against experimental data, where a mean percent error of −1.2% was recorded. Results revealed an increase in the radial distribution of cuttings transport velocity in the wide annular region as the consistency index, K, and the flow behavior index, n, increase. Nonetheless, increasing the yield stress, τ o, had insignificant effect on the cuttings transport velocity. Three-dimensional profiles showed how cuttings preferred to travel in less resistant flow area, whereas cuttings concentration builds up in the narrow annular region. Furthermore, annular frictional pressure losses also increased asK, n, andτ o increased. This study serves as a guide to properly optimize drilling fluid rheological properties for efficient cuttings transport and equivalent circulating density (ECD) management in narrow annular drilling.